Brokohan Tradition: History, Values and Meaning in Tunggalpager Village, Mojokerto - Laili, Azizah Nur (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This article aims to describe the history, values, and meaning of the Brokohan tradition, which is a traditional ceremony of welcoming a baby's birth that is held in Tunggalpager Village, Mojokerto. The Brokohan tradition is one of the traditions originating from Indonesia, especially from the Javanese community. This Brokohan tradition is used to express gratitude and joy for the smooth and safe birth process. This article uses ethnographic and sociological approaches, where the ethnographic approach is used to find out the processes and traditional values that exist in society. While the sociological approach is used to determine social values in the community in the village of Tunggalpager, Mojokerto. In this article, the author uses a method in the form of gathering sources, verification, interpretation, and writing. This article examines several aspects, namely the historical background, social dynamics, and the philosophical values implicit in the Brokohan tradition. It is this aspect that influences the community to get to know deeper the meaning and values so that they do not just carry out their activities.